Beneficial effects of quercetin on rat urinary bladder after spinal cord injury - ŞENER, AZİZE; ŞENER, GÖKSEL; TİNAY, İLKER; ÇETİNEL, ŞULE; TARCAN, TUFAN; ŞENER, TARIK EMRE (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2013)
Background: Spinal cord injury (SCI) leads to an inflammatory response and generates oxidative stress, which has deleterious effects on the function of several organ systems, including the urinary bladder. The present study was designed to investigate the putative beneficial effect of quercetin against SCI-induced bladder damage. Materials and methods: In order to induce SCI, a standard weight-drop method that induced a moderately severe injury (100 g/cm force) at T10 was used. Injured animals were given either 20 mg/kg quercetin or vehicle 15 min post injury and repeated twice daily for 7 d. After decapitation, bladder strips were placed in organ bath and isometric contractions to carbachol (10(-8) to10(-4) M) were recorded. In order to examine oxidative tissue injury, luminol chemiluminescence, nitric oxide, malondialdehyde, and glutathione levels and superoxide dismutase, myeloperoxidase, and caspase 3 activities of bladder tissues were measured along with histologic evaluations. Proinflammatory cytokines tumor necrosis factor alpha, interleukin 1 beta, and interleukin 6 were also assayed in blood samples. Results: In the injured animals, the contractile responses of the bladder strips were lower than those of the control group and were reversed by treatment with quercetin. On the other hand, increase in nitric oxide, malondialdehyde, luminol chemiluminescence levels, and myeloperoxidase and caspase 3 activities of tissues in the SCI group were significantly reversed by quercetin treatment. Similarly, plasma cytokine levels, which were elevated in the vehicle-treated SCI group, were reduced with quercetin treatment. Furthermore, treatment with quercetin also prevented the depletion of tissue glutathione levels and superoxide dismutase activity seen in the SCI group. Conclusions: According to the results, quercetin exerts beneficial effects against SCI-induced oxidative damage through its anti-inflammatory and antioxidant effects. (c) 2013 Elsevier Inc. All rights reserved.
Keywords: Quercetin; Spinal cord injury; Anti-inflammatory; Antioxidant; Caspase 3; Bladder; OXIDATIVE STRESS; EXPERIMENTAL-MODEL; ANTIOXIDANT; ANTAGONIST; PATHWAYS; ISCHEMIA; PROTECTS; DEFICITS; TRAUMA; DAMAGE